THE EFFECT OF BURNOUT (FATIGUE) ON ENGAGEMENT EMPLOYEES PERMANENT EMPLOYEES AT PT. INDOSRPING Tbk GRESIK - Asyhar, Muhammad Ali; Wicaksono, Awang Setiawan; Fastari, Chandrania (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to see whether or not there is a Burnout effect on the involvement of permanent employees of PT. Indospring Tbk. Employee engagement is an enthusiastic attitude of employees in doing their jobs, which is because employees put their energies into work and are in line with the company's strategic priorities. (Schaufeli et.al, 2002). Burnout is an emotional syndrome, depersonalization, and reduced personal achievement that can occur among individuals who work with people in multiple capacities (Maslach, 1996). This research was conducted on permanent employees who work at PT. Indospring Tbk Gresik with a sample size of 90 respondents. The data collection tools used are the Maslach Burnout Inventory (MBI) scale (22 valid items) compiled by Masclach (1996), the Ultrech Work Engineer Scale (UWES) (17 valid items) compiled by Schaufeli & Bekker (2004). The reliability of the employee engagement scale (r) is 0.930, and the reliability of the burnout scale (r) is 0.859 which means that it is lack of reliability. The data analysis used in this study is non-parametric statistics with non-linear regression test techniques with the help of SPSS 25.0 for Windows. Based on the analysis of research data using non-linear regression test, it can be concluded that the employee engagement variable by the burnout variable with a mathematical equation y = 83.405 - 0.331x. It can be accepted that Ho is rejected and Ha is accepted, so the simple non-linear regression analysis shows that there is a variable effect, namely fatigue of permanent employees of PT. Indospring Tbk. Gresik